Political Communication in Mass Media News in the City of Medan: Dynamics of Contemporary Society - Abdul Rasyid; Erwan Efendi; Afwan Syahril Manurung (Journal of General Education and Humanities, 2026)
This study aims to analyze political communication in mass media reporting in Medan and its implications for contemporary social dynamics. The research focuses on patterns, forms, and impacts of political communication in shaping public responses at the local level. This study employs a qualitative descriptive-analytical approach. Primary data were collected through in-depth interviews with six purposively selected informants: two journalists, two mass media editors, one political communication academic, and one active media audience member. Secondary data were collected through documentation and literature studies, particularly the analysis of mass media reporting. Data collection techniques included in-depth interviews, non-participant observation, and document analysis, while data analysis followed the stages of data reduction, data display, and conclusion drawing. Data validity was ensured through source and method triangulation. The findings, derived from both interview data and analysis of media reports, indicate that political communication in Medan’s mass media functions not only as a channel for delivering political information but also as a mechanism for framing issues, personalizing political actors, and dramatizing conflicts. The forms of political communication identified include informative, persuasive, symbolic, interpretive, and confrontational modes. These practices contribute to increased public sensitivity toward local political issues, the shaping of political images of key actors, and the emergence of fragmented perceptions within contemporary society.